An examination of dysfunctional attitudes and extreme response styles as predictors of relapse in guided internet‐based cognitive behavioral therapy for depression. Issue 6 (21st April 2020) - Ezawa, Iony D.; Forand, Nicholas R.; Strunk, Daniel R.
Abstract: Objectives: Internet‐based cognitive behavioral therapy (iCBT) is an effective treatment option for depression, but its long‐term effects are not well understood. We investigate for whom iCBT may have more enduring effects by evaluating dysfunctional attitudes as predictors of relapse. Methods: The sample consists of 31 iCBT responders (20 women, average age 31.6) who were followed for 1 year. Results: Higher Dysfunctional Attitudes Scale scores predicted higher risk of relapse (hazard ratio = 1.98). This relation remained significant when controlling for high style (dysfunctional) or content (functional) responses. Having relatively more positive extreme responses on style rather than content items did not predict risk of relapse. Conclusions: Our results were consistent with the value of differentiating an extreme style of responding from otherwise endorsing belief in dysfunctional attitudes. Research that refines our understanding of patients' individual risk for relapse has the potential to inform how treatment might be individually tailored.